Comparative Efficacy of Different Treatment Regimens of Miticidal Drugs in the Clinical Management of Canine Generalized Demodicosis - Parwari, Mayank; Mandali, Ghanshyam C.; Parmar , Jignasha M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study compared the efficacy of amitraz, doramectin, imidacloprid + moxidectin, test product (Green clean), and its  combinations in the clinical management of canine generalized demodicosis. A total of 48 positive cases of generalized demodicosis  were selected for the therapeutic trial. The affected dogs were divided into 6 groups, viz., A, B, C, D, E, and F; each group comprised 8  dogs. Six healthy dogs negative for demodectic mites were also used as control (group G) for comparison. The response to treatment was  assessed by conducting a clinical examination and parasitological examination of cases at weekly intervals included in the therapeutic  trial till clinical recovery (4-7 weeks) or treatment failure. Treatment regimens comprising of a combination of systemic miticidal drugs  (doramectin @ 600 µg/kg b.wt. s/c weekly) and a topical miticidal compound (amitraz @ 500 ppm spray weekly or test product 5%  spray twice daily) with supportive therapy were more efficacious in resolving the lesions and eliminating the mites than the treatment  regimens having single drug (doramectin/amitraz/test product). The combination therapy, along with supportive therapy with benzyl  peroxide shampoo, produced appreciable therapeutic results. There was no significant difference between different treatment groups,  except Group D (test product), which took a long time for clinical cure.
Keywords: Amitraz; Canine generalized demodicosis; Doramectin; Imidacloprid Moxidectin; Test product; Treatment regimen